Ebola: An Update for the Dentist - Ruchi D Raval , Surendra Lodha (RUHS Journal of Health Sciences, 2023)
A large eruption of Ebola virus disease was reported in March 2014 in areas of West Africa. World Health Organization declared this outburst as the largest a Public Health Emergency in 2014. The spread of virus is rapid with squat incubation period. It has been found to have high rate of mortality and morbidity making the disease a massive distress. To curb this epidemic, the health care professionals should play a dynamic role in treatment and prevention. Dentist, being a part of the health safety team should also have profound knowledge about the disease. The article provides precise guidelines to orient the dentists towards diagnosis, screening, precautions and disinfection while managing Ebola infected patients. Data was collected using electronic media consisting of articles, books, and websites.